Opportunity Assessment to Strengthen Collective Land Tenure Rights in FCPF Countries - World Bank (World Bank, Washington, DC, 2021)
Governments, development institutions, and the private sector are increasingly turning to nature-based solutions to address the world’s climate and biodiversity crisis. Countries, corporations, and investors are increasingly looking to forest- and land-based emission reduction programs (ERPs) to achieve early mitigation gains while they develop longer-term strategies and solutions to cut their greenhouse gas emissions. Central to emerging natural climate solutions are efforts to reduce deforestation and forest degradation while encouraging restoration, conservation, and sustainable use of forests in developing countries. The Forest Carbon Partnership Facility (FCPF), which became operational in June 2008, is a global partnership focused on reducing emissions from deforestation and forest degradation, forest carbon stock conservation, the sustainable management of forests and enhancement of forest carbon stocks (REDD+). Communal land and forest tenure rights for Indigenous Peoples and local communities (IPLCs) is critical for the success of emission reduction program (ERP) implementation. The remainder of this report is structured as follows. Section 2 provides an overview of the analytical and methodological approach of the study. Section 3 discusses core findings about the nature and range of emergent opportunities associated with efforts to advance, strengthen, and leverage rights and presents the main opportunities in six selected countries. Section 4 discusses lessons learned and cross-cutting areas for further development of rights recognition as a global process. Section 5 provides a summary of the country profiles.